1988
DOI: 10.1136/hrt.59.6.690
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatitis after parenteral amiodarone administration.

Abstract: Amiodarone is believed to have caused acute hepatitis 24 hours after intravenous administration in two patients in whom no other alternative cause of hepatitis was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…It is associated with extracardiac side effects, including asymptomatic hepatic dysfunction in 15-40% of patients [1], which resolves once the drug is either discontinued or the dose reduced and severe liver disease in the form of liver failure or death, which has been reported in 0-3% of cases [2]. One large series reported mild rise in liver enzymes in 23% (14-82%) of patients on orally administered amiodarone, of whom only 0.5% developed clinically overt disease [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with extracardiac side effects, including asymptomatic hepatic dysfunction in 15-40% of patients [1], which resolves once the drug is either discontinued or the dose reduced and severe liver disease in the form of liver failure or death, which has been reported in 0-3% of cases [2]. One large series reported mild rise in liver enzymes in 23% (14-82%) of patients on orally administered amiodarone, of whom only 0.5% developed clinically overt disease [3].…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits drugtransporter P-glycoprotein by impairing its adenosine triphosphatase (ATPase) activity and inhibiting CYP3A4, leading to higher concentrations of amiodarone. It has therefore been proposed that despite acute derangement of liver enzymes following intravenous (IV) amiodarone i.v., oral administration can still be safe [1].…”
Section: Discussionmentioning
confidence: 99%
“…its major metabolite, has not yet been clarified [9]. ' Early acute hepatitis due to parenteral amiodarone administration has been pre viously described in only 4 cases, as far as we know [1][2][3]. In all instances, the drug infu sion was immediately stopped.…”
Section: Discussionmentioning
confidence: 99%
“…1 Acute hepatotoxicity following intravenous (IV) amiodarone administration has been reported in several collections of adult case studies. [3][4][5] In 2005, Ra¨tz Bravo et al 6 reviewed 25 such adult cases reported between 1986 and 2002. Most cases occurred in patients aged 50 to 70 years with atrial tachyarrhythmia.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have noted that oral amiodarone therapy is well tolerated in patients even following acute hepatitis with parenteral therapy. 3,20 However, onset of action following oral administration is estimated to be 2 to 3 days, 21 which is not an acceptable time course for a patient with hemodynamic compromise in the critical care environment. Furthermore, given the potential for multiorgan dysfunction in patients with critical illness, poor gastrointestinal function may lead to unreliable absorption.…”
mentioning
confidence: 99%